Pengaruh Informasi Nilai Gizi Pada Kemasan Terhadap Pemilihan Camilan Pada Mahasiswa Pendidikan Tata Boga Universitas Negeri Medan - Atika Putri; Salsa Billa; Febrika Hajanah Triasti; Fatma Tresno Ingtyas; Laurena Ginting (Pusat Riset dan Inovasi Nasional, 2026)
Contemporary lifestyle patterns among university students have driven a substantial increase in the consumption of packaged food products, yet nutritional awareness remains suboptimal. This investigation seeks to examine the extent to which nutritional labeling on food packaging influences snack selection behavior among Culinary Education students at State University of Medan. The research employed a quantitative correlational design with 80 purposively selected participants. Data collection utilized structured questionnaires, subsequently analyzed through SPSS software encompassing validity testing, reliability assessment, normality verification, simple linear regression analysis, and t-test procedures. Findings demonstrated that all questionnaire components satisfied validity and reliability standards, data distribution conformed to normality assumptions, and a statistically significant positive correlation existed between nutritional label attention and snack selection patterns (t = 4.556; p < 0.05). These results suggest that heightened student attention to nutritional information correlates directly with more judicious snack selection practices.